IT-integrated design collaboration engagement model for interface innovations - Delavari, Naeimeh; Ibrahim, Rahinah; Sheik Said, Normahdiah; Abdullah, Muhamad Taufik (World Scientific and Engineering Academy and Society, 2013)
Due to the advent of computer-based technologies, data sharing and communication in collaborative design environments have significantly improved. However, current systems' interfaces do not support mutual understanding among professional design team members. This only contributes to increasing levels of miscommunication and lesser understanding among design professionals in IT-integrated design collaboration processes. The purpose of this paper is to understand and nurture engagement of design professionals within the building and construction sectors to the computing system interfaces, so they will actively participate in ITintegrated design collaborations. This study utilizes Grounded Theory Methodology to explicate our understanding about engaging design professionals. While control and feedback are common parameters of engagement in prior models, the study found the need to add functionality to engage design professionals in ITintegrated collaborative interfaces. These parameters would enable design professionals to mitigate process rigidity caused by inefficient knowledge allocation, knowledge retrieval and decision-making control. Additionally, they would also mitigate against inadequate user performance, which resulted in operational deficiency. Thus, the present IT-integrated design collaboration engagement model is expected to increase communication and collaboration among design professionals. By facilitating user-friendlier interfaces, they will be motivated to adopt collaborative technologies thereby encouraging them to develop their proficiencies for working in global collaborative projects.